1987
DOI: 10.2737/psw-rp-187
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of <em>Eucalyptus-Albizia</em> mixtures vary by site on Hawaii Island

Abstract: Plantings of Eucalyptus sa ligna (right, foreground) and Albizia falcataria (left, background) on Hamakua Coast of Hawaii Island.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Similarly, the success of certain mixed-species combinations in field trials has depended on site factors. For example the facilitative effect of higher N availability appears more likely to increase growth on sites where N is a major limiting resource (Binkley, 1992;Binkley and Green, 1983;DeBell et al, 1987;Khanna, 1997Khanna, , 1998. On sites with low N availability, the N-fixing species Facaltaria moluccana, Alnus rubra and Lupinus arboreus increased the growth of Eucalyptus saligna, Pseudotsuga menziesii and Pinus radiata respectively (Beets and Madgwick, 1988;Binkley, 1983Binkley, , 2003Binkley et al, 1992bBinkley et al, , 2003aDeBell et al, 1987).…”
Section: Implications For Mixed-species Systemsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, the success of certain mixed-species combinations in field trials has depended on site factors. For example the facilitative effect of higher N availability appears more likely to increase growth on sites where N is a major limiting resource (Binkley, 1992;Binkley and Green, 1983;DeBell et al, 1987;Khanna, 1997Khanna, , 1998. On sites with low N availability, the N-fixing species Facaltaria moluccana, Alnus rubra and Lupinus arboreus increased the growth of Eucalyptus saligna, Pseudotsuga menziesii and Pinus radiata respectively (Beets and Madgwick, 1988;Binkley, 1983Binkley, , 2003Binkley et al, 1992bBinkley et al, , 2003aDeBell et al, 1987).…”
Section: Implications For Mixed-species Systemsmentioning
confidence: 96%
“…On sites with low N availability, the N-fixing species Facaltaria moluccana, Alnus rubra and Lupinus arboreus increased the growth of Eucalyptus saligna, Pseudotsuga menziesii and Pinus radiata respectively (Beets and Madgwick, 1988;Binkley, 1983Binkley, , 2003Binkley et al, 1992bBinkley et al, , 2003aDeBell et al, 1987). However, the same species combinations were not successful (similar or lower productivity in mixtures than monocultures) on other sites where N availability was higher (Binkley, 1983;Binkley et al, 1992b) or the relative availability of other resources such as water and P were the major growth limiting resources (DeBell et al, 1987;Smethurst et al, 1986). When the interactions between species reduce the competition for a major growth limiting resource, mixtures are more productive than monocultures.…”
Section: Implications For Mixed-species Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…This predicament is often a direct result of the fact that seemingly "unimportant" species had been playing a role in maintaining ecosystem productivity (35). Mixed stands may produce more total biomass than single-species stands on some sites (17,82). The identification of such "overproduction" scenarios is an objective of much recent agricultural research into multiple cropping.…”
Section: Sustaining Productivitymentioning
confidence: 99%
“…Mixtures with leguminous trees, such as Acacia and Albizia, have been evaluated and appear promising (DeBell et al 1985). Research in Hawaii has centered on determination of optimum ratios of Eucalyptus and Albizia in such mixtures (DeBell et al 1987;DeBell et al 1989;Whitesell et al 1993). These studies have demonstrated the effects of site differences, species proportion, and rotation length on benefits to be derived from mixed plantations of the two species.…”
Section: Eucalyptus -Albizia Mixturesmentioning
confidence: 99%